UPGRADES HIGH SCHOOL STUDENT CRITICAL THINKING USING GUIDED INQUIRY LEARNING - MAULIDIYAH, FITROTUL; , MADLAZIM (Inovasi Pendidikan Fisika, 2019)
AbstractThis research aim are to describe the increase of critical thinking ability and quality of learning process with guided inquiry model in high school learners. This research using ?group pre-test and post-test design? with one experimental class and two replication classes. Data will analyzed with some techniques : paired t-test analysis and normalized gain for pre-test and post-test result than analyze of inquiry learning process. The results showed that: (1) the average assessment of learning process using guided inquiry has excellent category, (2) an increase of critical thinking ability in third grade sequentially got 0.35 (medium), 0.59 (medium) and 0.74 (high) in scores and the category. Overall based on the result, implementation of guided inquiry can improve student critical thinking ability about global warming topic.Keywords : Guided inquiry, Critical thinking ability, Global Warming. AbstrakPenelitian ini bertujuan untuk mendeskripsikan peningkatan kemampuan berpikir kritis dan kualitas keterlaksanaan pembelajaran model inkuiri terbimbing pada peseerta didik SMA. Penelitian ini menggunakan desain group pre-test and post-test dengan 1 kelas eksperimen dan 2 kelas replikasi. Analisis data menggunakan teknik analisis uji t-berpasangan dan gain ternormalisasi untuk hasil pre-test dan post-test kemudian analisis keterlaksanaan pembelajaran inkuiri. Hasil penelitian menunjukkan (1) rata-rata penilaian keterlaksanaan pembelajaran menggunakan inkuiri terbimbing berkategori sangat baik. (2) peningkatan kemampuan berpikir kritis di ketiga kelas secara beurutan mendapatkan skor dan kategori 0,35 (sedang), 0,59 (sedang) dan 0,74 (tinggi). Kesimpulan penelitian ini adalah bahwa pembelajaran menggunakan model inkuiri terbimbing dapat meningkatkan kemampuan berpikir kritis peserta didik.Kata Kunci : Inkuiri Terbimbing, Kemampuan Berpikir kritis, Pemanasan Global.